2020
DOI: 10.1242/dev.196055
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic cleavage of Slit by the Tolkin protease converts an axon repulsion cue to an axon growth cue in vivo

Abstract: Slit is a secreted protein that has a canonical function of repelling growing axons from the CNS midline. The full-length Slit (Slit-FL) is cleaved into Slit-N and Slit-C fragments, which have potentially distinct functions via different receptors. Here we report that the BMP-1/Tolloid family metalloprotease, Tolkin (Tok), is responsible for Slit proteolysis in vivo and in vitro. In tok mutants lacking Slit cleavage, midline repulsion of axons occurs normally, confirming that Slit-FL is sufficient to repel axo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Our observations that tok overexpression inhibits proliferation and impairs wing growth suggest that tok is unlikely to do so through activation of Dpp. Consistent with tok having additional cleavage targets, recent studies have revealed functions in proteolytic cleavage of the axon-guidance protein Slit ( Kellermeyer et al, 2020 ). Given the significant growth inhibitory functions of tok in the wing, unbiased approaches to identify pro-proliferative targets will be of great interest.…”
Section: Discussionmentioning
confidence: 95%
“…Our observations that tok overexpression inhibits proliferation and impairs wing growth suggest that tok is unlikely to do so through activation of Dpp. Consistent with tok having additional cleavage targets, recent studies have revealed functions in proteolytic cleavage of the axon-guidance protein Slit ( Kellermeyer et al, 2020 ). Given the significant growth inhibitory functions of tok in the wing, unbiased approaches to identify pro-proliferative targets will be of great interest.…”
Section: Discussionmentioning
confidence: 95%
“…As another example, Egr-2 might also control the influence of extracellular matrix or secreted cues that influence remodeling, since numerous proteases are dysregulated in egr-2(RNAi) regenerates (Table S1). Intriguingly, the Drosophila metalloprotease Tolkin cleaves Slit and converts it from a repulsive to a growth-promoting ligand 78 . A similar reduction in post-translational Slit-1 processing in egr-2(RNAi) regenerates could increase, rather than decrease, Slit-1-mediated repulsion, inhibiting midline fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, it consists of a putative signal peptide, four leucine-rich repeats (LRRs), 7 ( Drosophila SLIT) to 9 (vertebrate SLIT) epidermal growth factor (EGF) repeats, a laminin G domain, and a cysteine-rich domain ( Rothberg et al, 1990 ; Rothberg and Artavanis-Tsakonas, 1992 ) ( Figure 1 ). Most SLIT proteins can be fragmented by an unknown protease between the fifth and sixth EGF repeats, with a conserved proteolytic site ( Brose et al, 1999 ; Wang et al, 1999 ; Patel et al, 2001 ; Kellermeyer et al, 2020 ).…”
Section: Structure and Characteristics Of Slit Proteinsmentioning
confidence: 99%